Global Flows of Competence-based Approaches in Primary and Secondary Education - Kathryn Anderson-Levitt (Cahiers de la Recherche sur l'Education et les Savoirs)
This essay reviews the history of competence-based approaches and related reforms in the domain of primary and secondary education, seeking to explain how they have come to appear in various countries and international organizations from the 1990s to the present. It shows that competence-based approaches are widespread but not quite global in their reach; notably, they have not been implemented in the United States, contrary to claims by some advocates. The broadest plausible explanation of their spread is that integrative competence-based approaches serve employers in the new global economy although a few key adopters have nevertheless terminated their reforms. Thus would-be adopters should exercise a certain degree of caution.